Do Financial Ratios Signal Sukuk Credit Quality? Evidence from Indonesian Corporate Sukuk Ratings - Falikhatun - Falikhatun; Arif Lukman Santoso; Susanto Tirtoprojo; Hasim Hasim (Integrated Journal of Business and Economics (IJBE), 2026)
This paper aims to obtain empirical evidence of the influence of financial dimensions on ratings of green sukuk. The variables used in this study include corporate sukuk ratings as the dependent variable, and financial dimensions consisting of profitability, liquidity, and leverage as the independent variables. The population of this study is corporate sukuk rated by PT PEFINDO in the period 2016-2022. The sampling technique was purposive sampling. The results of this study indicate that Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER) simultaneously influence corporate sukuk ratings. Further, partial analysis shows that ROE has a positive effect on corporate sukuk ratings, but CR and DER negatively affect corporate sukuk ratings. The implication for issuers is that they must maintain financial performance and debt ratios to achieve optimal rating results. A good rating will make sukuk issuance costs more efficient, thereby reducing the company's ujrah of corporate sukuk.